Why do students choose to study on engineering foundation year programmes within the UK?. (2nd January 2023) - Wint, Natalie
ABSTRACT: In recent years there have been calls to increase both the number and diversity of engineering graduates within the UK. In addition to this, technological advancement and the need to solve complex socio-economic problems, have contributed toward a shift in the skills and abilities that practicing engineers require. Such changes have led to an increased focus on attracting students from a variety of backgrounds, who may want to study engineering for an increasing number of reasons. There is thus an interest in the factors which influence students to apply to study engineering. This paper describes the use of digital storytelling to understand the reasons that 82 engineering foundation year students from one UK-based institution, chose to study engineering. The research makes use of social cognitive career theory. The findings demonstrate the complex way in which environmental contextual factors influence self-efficacy, learning experiences, and career expectations. Based on these findings, some suggestions are made for attracting and retaining engineering students.